Effectiveness of Capital Restrictions: Do Regional and Income Differences Matter? - Maria Socorro Gochoco-Bautista; Ruth H. Francisco (Asian Development Bank (ADB), 2011)
This study examines the differences in the effectiveness of de jure capital restrictions across economies in different regions (Asia versus non-Asia) and with varying income levels. It uses a panel of 45 economies over the period 1995– 2007. The results show that differences in regional and income levels matter for the effectiveness of capital restrictions.
hdl:11540/2020
Keywords: 330; Kapitalverkehrskontrolle; Nationaleinkommen; Vergleich; Asien; Welt